2018
DOI: 10.1016/j.pedneo.2017.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Acute peritoneal dialysis in neonatal intensive care unit: An 8-year experience of a referral hospital

Abstract: Peritoneal dialysis is an effective route of renal replacement therapy in the neonatal period for management of metabolic disturbances as well as renal failure. Although major complications of the procedure are uncommon, these patients still have a high mortality rate due to serious nature of the underlying primary causes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
44
0
12

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(58 citation statements)
references
References 23 publications
1
44
0
12
Order By: Relevance
“…However, to date, there is no guideline-based evidence regarding the indications and methods of RRT for premature infants. If renal failure has not been resolved despite medical treatments, the timing and method of dialysis are selected on the basis of the decision of the primary care physician [ 8 , 20 , 21 ]. As a result, the prognosis of premature infants with AKI treated with RRT is expected to change.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, to date, there is no guideline-based evidence regarding the indications and methods of RRT for premature infants. If renal failure has not been resolved despite medical treatments, the timing and method of dialysis are selected on the basis of the decision of the primary care physician [ 8 , 20 , 21 ]. As a result, the prognosis of premature infants with AKI treated with RRT is expected to change.…”
Section: Discussionmentioning
confidence: 99%
“…Some complications associated with PD in premature infants include mechanical dysfunctions, such as dialysate leakage and catheter obstruction requiring revision or reinsertion, intraperitoneal hemorrhage, and bowel perforation [ 17 , 20 , 32 ]. Peritoneal fluid leakage around the PD catheter and along the tunnel is a serious problem that can increase the risk of bacterial and fungal peritonitis [ 21 , 33 ]. In this study, the complications observed in relation to PD were mainly caused by catheter-related dialysate leakage, which was resolved after adjustment of the dwell volume or reinsertion of the catheter on the other side.…”
Section: Discussionmentioning
confidence: 99%
“…Some complications associated with PD in premature infants include mechanical dysfunctions, such as dialysate leakage and catheter obstruction requiring revision or reinsertion, intraperitoneal hemorrhage, and bowel perforation [17,20,29]. Peritoneal fluid leakage around the PD catheter and along the tunnel is a serious problem that can increase the risk of bacterial and fungal peritonitis [21,30]. In this study, the complications observed in relation to PD were mainly caused by catheterrelated dialysate leakage, which was resolved after adjustment of the dwell volume or reinsertion of the catheter on the other side.…”
Section: Discussionmentioning
confidence: 99%
“…Los baños de diálisis deben realizarse con permanencias cortas (de 30 a 60 min) y con bajos volúmenes de infusión (de 10 a 30 ml/kg). 13 Dado que estos niños tienen función renal normal, durante la diálisis continua, debe chequearse el medio interno para evitar su alteración. n…”
Section: Discussionunclassified